Reward Processing and Circuit Dysregulation in Posttraumatic Stress Disorder - Lokshina, Yana; Nickelsen, Tetiana; Liberzon, Israel (Frontiers in Psychiatry, 2021)
Past decades have witnessed substantial progress in understanding of neurobiological mechanisms that contribute to generation of various PTSD symptoms, including intrusive memories, physiological arousal and avoidance of trauma reminders. However, the neurobiology of anhedonia and emotional numbing in PTSD, that have been conceptualized as reward processing deficits - reward wanting (anticipation of reward) and reward liking (satisfaction with reward outcome), respectively, remains largely unexplored. Empirical evidence on reward processing in PTSD is rather limited, and no studies have examined association of reward processing abnormalities and neurocircuitry-based models of PTSD pathophysiology. The manuscript briefly summarizes “state of the science” of both human reward processing, and of PTSD implicated neurocircuitry, as well as empirical evidence of reward processing deficits in PTSD. We than summarize current gaps in the literature and outline key future directions, further illustrating it by the example of two alternative explanations of PTSD pathophysiology potentially affecting reward processing via different neurobiological pathways. Studying reward processing in PTSD will not only advance the understanding of their link, but also could enhance current treatment approaches by specifically targeting anhedonia and emotional symptoms in PTSD patients.